Comparison of date-palm wastes and perlite as culture substrates on growing indices in greenhouse cucumber - Ahmad Mohamadi Ghehsareh; Maliheh Hematian; Mahmoud Kalbasi (International Journal of Recycling of Organic Waste in Agriculture)
Different substrates have several materials which could have direct and/or indirect effects on plant growth and development. Therefore selecting the best substrate between the various materials is imperative to plant productivity. This research was carried out with using a completely randomized design with three treatments and seven replications. The treatments were including perlite, date-palm waste and soil. During plant growth irrigation rate, temperature, humidity, pest control for all treatments were similar. Cucumis Stativus cultivar was used for seeds. During plant growth Papadopolus formula with fertigation method used for nutrient solution. Some physiochemical characteristics of cultivation substrates were measured. The growth indices of cucumber plant were measured at the end of growth period. Results showed that higher amount of yield, biomass weight, SD, plant height, root weight, LAI and fruit TSS related to date-palm waste that had a significant difference with soil at 5% level but generally had not any significant difference at 5% level as compared with perlite substrate.